2019
DOI: 10.3390/su11041112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lean Manufacturing Practices on Firms’ Sustainable Performance: Lean Culture as a Moderator

Abstract: Nowadays, manufacturing firms are pressured by governments, non-governmental organizations and customers to operate in a sustainable manner. Although lean practices may provide environmental, social, and financial benefits to firms, their effect on sustainable performance is ambiguous. The aim of this study is to examine the effect of lean manufacturing practices on firms’ environmental performance by considering lean culture as a moderator. Data were gathered through a survey of 187 manufacturing firms in Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 88 publications
5
117
1
7
Order By: Relevance
“…Klassen and Corbet in their study about the impact of lean manufacturing on the firm"s sustainability showed better financial returns through gaining new customers, eliminating cost through reducing waste and competitive differentiation (Iranmanesh et al, 2019). According to Lenox and King (2001), in their study about lean manufacturing and environmental performance, discussed that lean practices contribute to financial performance by carrying down the managerial cost by lowering pollution, they agree that there is a positive relationship between financial performance and lean manufacturing (King and Lenox, 2001).…”
Section: Relationship Between Lean Manufacturing and Financial Performentioning
confidence: 99%
“…Klassen and Corbet in their study about the impact of lean manufacturing on the firm"s sustainability showed better financial returns through gaining new customers, eliminating cost through reducing waste and competitive differentiation (Iranmanesh et al, 2019). According to Lenox and King (2001), in their study about lean manufacturing and environmental performance, discussed that lean practices contribute to financial performance by carrying down the managerial cost by lowering pollution, they agree that there is a positive relationship between financial performance and lean manufacturing (King and Lenox, 2001).…”
Section: Relationship Between Lean Manufacturing and Financial Performentioning
confidence: 99%
“…Establishing long-term relationships with key suppliers can capture the benefits of building learning routines and ensures both parties' sets of capabilities that are aligned and stay useful for future joint projects (Echtelt et al, 2006;Nimeh et al, 2018). Supplier relationship refers to the extent of interaction with the supplier to direct quality regards and guarantee justin-time delivery through taking into consideration the suppliers number, long-term relationships, and involving the suppliers in the design of the product and in the process of development and by giving feedback on suppliers' performance (Iranmanesh, et al, 2019). This paper proposed SRM as one of the most important LSC practice which also could be aligned with the source process in SCOR model.…”
Section: -1-2-2 Supplier Relationship Managementmentioning
confidence: 99%
“…Also, (Shah & ward, 2007) indicated customer involvement as one measure for lean production construct which focuses on the organization's customers and their needs. (Khanchanapong et al, 2014;Iranmanesh et al, 2019) showed how early customers' involvement in the process of product development allows the improvement of product development in a way that meets the needs of the customers and leads to cost reduction. CRM includes customer involvement by frequently and timely exchange of information with customers about (e.g.…”
Section: -1-2-4 Customer Relationship Managementmentioning
confidence: 99%
See 2 more Smart Citations